Accelerating Soe's Employee Innovative Work Behavior: the Effect of Transformational Leadership and Psychological Capital with Knowledge Sharing as Intervening Variable - Putri Anggraeni; Riani Rachmawati (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2023)
Innovation is essential in the current dynamic and competitive business environment. Therefore, the company must leverage innovative work behavior to all employees to continuously create new products/services and update the work process. Researchers and practitioners argue that proper leadership, positive psychological, and knowledge-sharing activities are relevant factors in encouraging and accelerating employees’ innovative work behavior. In order to improve State-owned enterprise (SOE) employees’ innovative work behavior and bear up previous research gaps, this study investigates whether transformational leadership and psychological capital encourage innovative work behavior in SOE employees, directly and indirectly, using knowledge-sharing as an intervening variable. The researcher processed clean data from 303 respondents who completed online questionnaires using the Structural Equation Modeling method. The result found that transformational leadership and psychological capital positively affected the innovative work behavior of SOE employees, both directly and through knowledge-sharing activities. However, the magnitude of psychological capital toward the innovative behavior of SOE employees directly and through knowledge-sharing activities is more substantial than transformational leadership. Furthermore, theoretical and practical implications are discussed. Furthermore, theoretical and practical implications are discussed. Lastly, the company can use the results to intervene in relevant factors to increase employee innovation.